Identification Of Liquefaction Hazard In The Coastal Area Of Merak-Anyer, Banten Based On Cpt And Spt Data - Eko Soebowo (Pusat Riset Kelautan, 2016)
The coastal area of Merak-Anyer, Banten is located in the high seismic zone therefore it is highly susceptible to seismic hazard such as liquefaction. Earthquake triggered liquefaction could cause destructions to buildings and infrastructures, thus it can hinder evacuation efforts during an earthquake event. Knowledge of the spatial distribution of liquefaction hazard potential in the coastal area is required as part of the hazard mitigation measures. This paper presents the results of the liquefaction hazard susceptibility analysis in Merak-Anyer, Banten based on geotechnical investigation. Liquefaction analysis was carried out using cone penetration test (CPT) and N-SPT methods with earthquake magnitude of 7, peak ground acceleration of 0.25 g and local groundwater level. Analysis results showed that all investigation points in the coastal area of Merak-Anyer are prone to liquefaction and its associated settlement. The high liquefaction zone includes the areas of Rencana Pelabuhan Cilegon, Cigading, Mercu Suar dan Cinangka which correlates with the occurrence of loose sand – loose silt at the surface to the depth of 10 m with cone resistance (qc) < 10 MPa and N-SPT <10.